Classification of Hospital of the Future Applications using Machine Learning - Zulkifli I.T.; Radzi N.A.M.; Aripin N.M.; Azmi K.H.M.; Samidi F.S.; Azhar N.A. (Institute of Electrical and Electronics Engineers Inc., 2024)
Effective health management is critical to ensure patients have access to necessary healthcare services. There are a number of challenges that can limit the provision of medical treatment, including a shortage of healthcare professionals, limited resources, and geographical barriers. Hospital of the Future (HoF) incorporates a number of technologies and innovations to improve the delivery of healthcare services and support effective health management. 5G network slicing has the potential to greatly enhance the capabilities of hospitals and the delivery of healthcare services. The network can be sliced into three main services